Bacteriological valuations of some powdered infant milk and antibiotic resistance estimation - Sameira S. Swilaiman; Lawin A. Omer; Suhaila N. Darogha (Erbil Dental Journal, 2022)
Background and objectives: Milk is one of the widely consumed products in the world, highly susceptible to contamination by microorganisms and it is also a suitable medium for the rapid growth and multiplication of bacteria at favorable temperatures, infant formula (baby milk) contain purified cow's milk whey and casein as a protein source, the high nutrient contents of infant formula provide a good growth medium for bacterial pathogens. This study aimed to evaluate the prevalence of bacterial contamination in powder milk sold in local market of Erbil city, and to determine their antibiotic susceptibility . Method: In a total of 12 samples of commercial dried milk products (infant powdered milk) used by consumers in Erbil state, biochemical and molecular identification were used for identification. A region of 16S rRNA gene were amplified by PCR to allow species identification, and the sensitivity of isolates to eight antibiotics was studied by using standard disc diffusion method Results: Eight samples of infant powdered milk (N = 12) were contaminated with (62.5%) Staphylococcus sp and (37.5%) Lactobacillus sp . In addition, Staphylococcus sp. resistance against AMC and E was between (72-69%) and the lowest resistance was against AMK and TE (25-28%). Lactobacillus species resistance was most frequently observed to E and AMC (88-83%), and lowest resistance was against CIP,TE ( 25-30%) Conclusion : The current study found that infant powdered milk used by consumers in Erbil state were contaminated with Staphylococcus sp. and Lactobacillus , these isolates exhibited multiple antimicrobial resistance. No significant differences were found between isolates against antibiotic resistances.